Розроблення та дослідження системи контролю параметрів технологічного процесу виготовлення халви - Григоренко, Ігор Володимирович; Григоренко, Світлана Миколаївна; Носова, І. В. (ВКФ "Фавор", 2019)
Розглянуто вирішення науково-практичного завдання вдосконалення системи контролю параметрів технологічного процесу виготовлення халви від створення структурної схеми до розроб лення схеми електричної принципової. Виконано опрацювання результатів прямих багаторазових вимірювань, отриманих за допомогою системи контролю, а саме, датчика вологості та температури (SHT21). Побудовано рівняння прямої й зворотної регресії та встановлено характер зв'язку між температурою та вологістю за допомогою коефіцієнтів парної кореляції. Розроблена система контролю надає можливість забезпечити відносну похибку вимірю- вання, не гіршу ніж 2,5 %. Система контролю пропонується для використання на заводах із виробництва халви з метою контролю основних параметрів технологічного процесу для забезпечення випуску якісної продукції.

The paper considers the solution of the scientific and practical problem of improving the system of control of the parameters of the technological process of halva production from the creation of the structural scheme to the development of the electrical circuit diagram. The results of direct multiple measurements obtained from the control system, namely the humidity and temperature sensor (SHT21), have been processed. The equations of direct and inverse regression were constructed and the nature of the relationship between temperature and humidity was established using the pair correlation coefficients. The developed control system makes it possible to provide a relative measurement error of not less than 2,5 %. Control systems are proposed for use at halva plants with the duty to control the basic parameters of the process to ensure the production of quality products. The measuring device includes the following primary measuring transducers: raw material moisture sensor (FIZEPR-SW100.11.x), air humidity sensor (SHT21), water temperature sensor, caramel mass, halves during mixing (DS18B20 Dallas Semiconductor model), temperature control sensor halva storage air (ADT7420). ATmega16 was used as the microcontroller. The proposed meter is capable of transmitting data up to 50 m over a 2,4 GHz radio channel with a SPI interface to the microcontroller. This transmission enables the nRF24L01 radio to operate at 2,4 GHz (Wi-Fi frequency). The need to improve the existing meter has been proved by the use of a radio channel due to the fact that at this time it is necessary to avoid using wired interfaces where possible, due to the inability, sometimes, to draw communication lines due to the presence of already installed equipment.
Development and Research of the System for Control of Parameters of Manufacture of Halva Technological Process
Keywords: похибка; вимірювання; точність; датчик вологості та температури; system; error; measuring; accuracy; control